121k views
2 votes
What is the solution to the following system of equations?

y=6x-11 //////
-2x-3y=-7

2 Answers

3 votes

Answer:

D . (2, 1)

Explanation:

User Flopga Slays
by
5.5k points
0 votes
y = 6x - 11
-2x - 3y = -7

Let's use substitution:

-2x - 3y = -7
-2x - 3(6x - 11) = -7
-2x - 18x + 33 = -7
-20x + 33 = -7
-20x = -40
x = 2

----

y = 6x - 11
y = 6(2) - 11
y = 12 - 11
y = 1

----

y = 6x - 11 => 1 ? 6(2) - 11 => 1 = 12 - 11 <--True
-2x - 3y = -7 => -2(2) - 3(1) ? -7 => -4 - 3 = -7 <--True

Answer:
x = 2
y = 1

Hope this helps!
User Jeff LaFay
by
5.9k points